Comparison of the Effects of Circuit Bodyweight Training and Jogging on the Reduction of Subcutaneous Fat Thickness in Obese University Students - Al Islamy, Abdil Hikam; Hayati, Hayati; Pelamonia, Shandy Pieter (STKIP PGRI Trenggalek, 2026)
Obesity among university students is a growing health problem influenced by low physical activity and sedentary lifestyles. One indicator used to assess obesity is subcutaneous fat thickness. This study aimed to compare the effects of Circuit Bodyweight Training and jogging on the reduction of subcutaneous fat thickness in obese university students. The study employed a quantitative experimental method with a pre-test and post-test control group design. The participants were obese students from the Physical Education Study Program at Universitas PGRI Adi Buana Surabaya, who were divided into a Circuit Bodyweight Training group, a jogging group, and a control group. The intervention was conducted for six weeks with a frequency of two sessions per week. Subcutaneous fat thickness was measured using a skinfold caliper. Data were analyzed using statistical tests at a significance level of 0.05. The results indicated that both training methods contributed to a reduction in subcutaneous fat thickness; however, Circuit Bodyweight Training resulted in a more significant reduction compared to jogging. Therefore, Circuit Bodyweight Training can be recommended as a more effective exercise method for reducing subcutaneous fat thickness in obese university students